Liver Function Tests in Workers with Occupational Exposure to Polychlorinated Biphenyls (PCBs): Comparison with Yusho and Yu-Cheng - Fischbein, Alf (Environmental health perspectives, 1985)
The results of liver function tests in a population manufacturing capacitors and transformers are presented. Two clinical field examinations were performed, one in 1976 when PCBs were still used in the manufacturing of the electrical equipment and one at the end of 1979, 2.5 years after discontinuation of PCBs use. A low prevalence of abnormal liver function tests was found and mean values for all tests were within normal laboratory ranges. At the initial examination, weak, but statistically significant correlations were found between log LDH and plasma levels of log HPCB (higher chlorinated congeners of polychlorinated biphenyls) and log TPCB (total polychlorinated biphenyls) among the female workers, while log γ-GTP correlated significantly only with log HPCB among the male workers. A significant increase to abnormal levels of γ-GTP was noted at the follow-up examination in both male and female workers, and preliminary results indicate significant correlations between γ-GTP and serum levels of PCBs among the male workers. These findings are in accordance with previously reported data on populations occupationally exposed to PCBs, but differ from hepatic biochemistry findings in accidental poisonings due to ingestion of cooking oil contaminated with PCBs and related compounds, i.e., polychlorinated dibenzofurans (PCDFs) and polychlorinated quaterphenyls (PCQs). Hence, the importance of considering the related compounds as etiologic factors in PCB poisoning is emphasized.